Pelatihan Praktikum Bioteknologi Sederhana: Pembuatan Kombucha untuk Guru Biologi MGMP Kota Yogyakarta - Susilawati, Puspita Ratna; Ladjar, Maria Esterlita Beto; Pamungkas, Robertus Bangkit; Hapsari, Intan Putri; Handoyo, Luisa Diana; Feroniasanti, Yoanni Maria Lauda (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Biology education in secondary schools faces challenges in implementing practical work that is relevant to the learning material, one of which is biotechnology. Musyawarah Guru Mata Pelajaran (MGMP) Kota Yogyakarta, or the Yogyakarta Biology Teacher Working Group, has identified an urgent need for training in a biotechnology experiment that is simple, applicable, and takes place in the context of school and community learning. This Pengabdian kepada Masyarakat (PkM) or Community Service Activities provided an innovative solution in the form of applicable kombucha-making training for biotechnology-supported practical learning. The goal of this activity was to improve the Biology Teacher Working Group's ability to implement appropriate kombucha-making training to support the biotechnology learning experience. This activity was carried out using a training method. The training participants were 22 teachers from 10 schools around Yogyakarta. The implementation of the training included delivering materials, practicing making kombucha, and collecting data. The data collection instruments included test questions and questionnaires. The PkM activity of simple biotechnology practical training through making kombucha for the biology teachers of MGMP Kota Yogyakarta was successfully implemented following the objectives, namely improving the teachers’ competence in terms of knowledge and skills, especially in carrying out biotechnology experiments. The teachers' training provided them with theoretical and practical knowledge about making kombucha, as well as kombucha's benefits, which could be applied in the contexts of education and society. The training also met the partners' expectations, specifically by providing alternative practical themes that were part of the learning materials and could be implemented in schools with limited resources. The next step in this PkM activity is to collaborate with MGMP partners to organize simple and applicable practical training, so that the training's impact is greater. Practical training can be a way for universities to help teachers improve their skills.